The Impact of Digital Storytelling and Spoken Storytelling to Improve Students’ Reading Comprehension Through Project Based Learning - Fatmawati, Eka; Rudi Hartono; Suwandi Suwandi (English Education Journal, 2024)
Reading is one of the most significant problems facing educators today because it one of the basic ways of acquiring information in our society and in academic setting in particular. Individual who can not read well is at a serious disadvantage with respect to educational and, consequently, vocational opportunities. Using an appropriate strategy will help to solve the problem. This study aims to analyse the impact digital storytelling and spoken storytelling to improve students’ reading comprehension. This study used mixed method research design, samples of this study were 72 students which divided into two group; X.2 as experiment who were taught by using digital storytelling group and X.3 as control group who were taught by spoken storytelling. Some instruments were used, such as test, interview, observation, and questionnaire. Pre-test was given before treatment then post-test was given after treatment. To measure student’s perception, questionnaire was given to all participant, and interview was given as representative of each group, while observation did in teaching learning process. The result of study revealed that teaching reading using digital storytelling was more significant than spoken storytelling, it can be seen from the mean result between pre-test and post-test. Students who got treatment by using digital storytelling has significant value in passing KKM. It also can be seen from students’ perception from questionnaire, the benefits using digital storytelling in reading were students contributed in teaching learning by utilising technology, improved their digital literacy, and increased their creativity. In briefly, digital storytelling can be used as alternative teaching reading in classroom, using Digital Storytelling improved not only reading comprehension but also student’s creativity, critical thinking, and collaboration or communication, such as mentioning in Profil Pelajar Pancasila. Meanwhile, for students, this research assisted students to be confident in learning English, use technology in appropriate way, and they can work together, for instance, discussing, delivering ideas, having meaningful learning English